APPLICATION OF GROUP INVESTIGATION MODEL TO INCREASE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Yuanita, Rizki; Degeng, I Nyoman Sudana; Sudarmiatin, Sudarmiatin (Journal of K6, Education and Management, 2018)
This research aims to improve student learning outcomes on care for living things through the application of group investigation model can theme. The research method was classroom action consisting two cycles with subjects were the 4th grade students of Pemurus Baru 1 Public Elementary School academic year 2017/2018, total sample 30 students, and data collected through evaluation test. The results showed that by using study group investigation, the student learning outcomes increase.